![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x+3=15\\ \Rightarrow2x=15-3=12\\ \Rightarrow x=\dfrac{12}{2}=6\\ ---\\ 28-3x=13\\ \Rightarrow3x=28-13=15\\ \Rightarrow x=\dfrac{15}{3}=5\\ ---\\ \left(x-1954\right).5=50\\ \Rightarrow x-1954=50:5=10\\ \Rightarrow x=10+1954=1964\\ ---\\ x-152:2=46\\ \Rightarrow x-76=46\\ \Rightarrow x=46+76=122\)
a, 2\(x\) + 3 = 15
2\(x\) = 12
\(x\) = 6
b, 28 - 3\(x\) = 13
3\(x\) = 28 - 13
3\(x\) = 15
\(x\) = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x-152:x=46\)
\(x^2\) - 152\(\) - 46\(x\) = 0
\(x^2\) - 23\(x\) - 23\(x\) + 529 - 681 = 0
\(x\)(\(x-23\)) - 23(\(x\) - 23) = 681
(\(x-23\))(\(x-23\)) = 681
\(\left[{}\begin{matrix}x-23=-\sqrt{681}\\x+23=\sqrt{681}\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=23-\sqrt{681}\\23+\sqrt{681}\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2^{x+2}+2^{x-1}+2^{x-2}=152\)
=> \(2^x.2^2+2^x:2+2^x:2^2=152\)
=> \(2^x.2^2+2^x.\frac{1}{2}+2^x.\frac{1}{4}=152\)
=> \(2^x.(4+\frac{1}{2}+\frac{1}{4})=152\)
=> \(2^x.\frac{19}{4}=152\)
=> \(2^x=32\)
=> \(2^x=2^5\)
=> x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Trl:
a) \(x+x+x+91=-2\)
\(\Rightarrow x.3+91=-2\)
\(\Rightarrow x.3=-2-91\)
\(\Rightarrow x.3=-93\)
\(\Rightarrow x=-93:3\)
\(\Rightarrow x=-31\)
b) \(-125-\left(3x+1\right)=-2.27\)
\(\Rightarrow-125-\left(3x+1\right)=-54\)
\(\Rightarrow\left(3x+1\right)=-125-\left(-54\right)\)
\(\Rightarrow\left(3x+1\right)=-125+54\)
\(\Rightarrow\left(3x+1\right)=-71\)
\(\Rightarrow3x=-71-1\)
\(\Rightarrow3x=-72\)
\(\Rightarrow x=-72:3\)
\(\Rightarrow x=-24\)
Hc tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
2x + 2 + 2x - 1 + 2x - 2 = 152
19 . 2x - 2 = 152
19 . 2x - 2/19 = 152/19
2x - 2 = 8
2x - 2 = 23
x - 2 = 3
x = 3 + 2
x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,-152-\left(3x+1\right)=\left(-2\right).\left(-77\right)\)
\(-152-\left(3x+1\right)=154\)
\(3x+1=-152-154\)
\(3x=306\)
\(x=-102\)
Vậy \(x=-102\)
\(b,234+\left(-334-x\right)=500\)
\(-334-x=266\)
\(x=-600\)
Vậy \(x=-600\)
\(c,\left(567-x\right)+121=-641\)
\(567-x=-762\)
\(x=1329\)
Vậy \(x=1329\)
Làm lại câu a :
a, -152-(3x+1)=(-2).(-77)
-152-(3x+1)=154
3x+1=-306
3x=-307
x=-307/3
Vậy x=-307/3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x-2).(x+4)=0
<=> hoặc x-2=0 hoặc x+4=0
<=> hoặc x=2 hoặc x=-4
Vậy x \(\in\){-4;2}
b) 2x2-3=29
=> 2x2=32
=> x2=16
<=> x=4
c) 45-(x-11)=-48
x-11 = 45-(-48)
x-11 = 45+48
x-11 = 93
x = 93+11
x = 104
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x + 1 5 2 − 9 25 = 0 ⇒ x + 1 5 2 = 9 25 ⇒ x + 1 5 = 3 5 x + 1 5 = − 3 5 ⇒ x = 2 5 x = − 4 5
b) x + 1 5 2 + 17 25 = 26 25 ⇒ x + 1 5 2 = 9 25 ⇒ x = 2 5 x = − 4 5
x - 152 : 2 = 46
x - 76 = 46
x = 46 + 76
x = 122
x - 152 : 2 = 46
x - 76 = 46
x = 76 + 46
x = 122